Analysis of Applied Media in Public Service Advertisements “Tetap Fokus di Jalan” - Nenden Suryamanah Annisa; Hade Nadia Husnia; Zakarias Sukarya Soetedja (Universitas Pendidikan Indonesia, 2022)
Public service advertising is a government program that aims to educate the public on good values from the state's point of view. As the name implies, public service advertisements contain the word